Designing A Mental Health Board Game to Promote Emotional Well-Being Among Adolescents: A Participatory Approach - Idyan, Zamna; Anggrainy, Verra; Arinda, Wittia; Diansyah, M. Valent (International Journal Scientific and Professional, 2025)
Adolescent mental health is a growing concern globally, with increasing cases of anxiety, depression, and emotional distress. Innovative interventions are needed to help young individuals develop better-coping strategies. This study aimed to design, develop, and evaluate a board game as an educational and therapeutic tool to enhance adolescents' mental health awareness and emotional regulation. The development process followed four stages: needs assessment, game design, prototype testing, and evaluation. Fifty adolescents aged 14–18 participated in the trial phase. Data were collected through surveys, interviews, and observations before and after gameplay. Evaluation indicators included reduction of stress and anxiety, emotional management skills, knowledge gain, and quality of social interaction. The game showed positive impacts on mental health literacy and emotional resilience. Participants reported increased awareness of emotional regulation (70%), reduced anxiety and stress levels (65%), enhanced communication comfort regarding mental health issues (65%), and improved peer social bonding (55%). The educational features and interactive elements were highly rated by the adolescents (average score: 4.6/5). The board game was an engaging and effective tool for promoting mental health education among adolescents. Its participatory and relatable approach allowed young players to explore emotional topics in a safe, playful, and collaborative environment. Further development and broader distribution are recommended to increase its accessibility and long-term impact.